A Semiotic Approach to Rhythm, Symbolism, and Signification in the Poem “Al-Shahada” by Ammar Ben Laqrichi - .salhi, brahim; .boudiaf, ahmedamine (El Omda in Linguistics and Discourse Analysis, 2026)
<section class="text-token-text-primary w-full focus:outline-none [–shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(–shadow-height) has-data-writing-block:pt-(–shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto R6Vx5W_threadScrollVars scroll-mb-[calc(var(–scroll-root-safe-area-inset-bottom,0px)+var(–thread-response-height))] scroll-mt-(–header-height)" dir="auto" data-turn-id="cb2ab366-e019-4f72-83b3-2583833e592b" data-testid="conversation-turn-13" data-scroll-anchor="false" data-turn="user"> <section class="text-token-text-primary w-full focus:outline-none [–shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(–shadow-height) has-data-writing-block:pt-(–shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto [content-visibility:auto] supports-[content-visibility:auto]:[contain-intrinsic-size:auto_100lvh] R6Vx5W_threadScrollVars scroll-mb-[calc(var(–scroll-root-safe-area-inset-bottom,0px)+var(–thread-response-height))] scroll-mt-[calc(var(–header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:e8f07b8e-ad4e-4d81-b9b3-92be614a64cd-6" data-testid="conversation-turn-14" data-scroll-anchor="false" data-turn="assistant"> <div class="text-base my-auto mx-auto pb-10 [–thread-content-margin:var(–thread-content-margin-xs,calc(var(–spacing)*4))] @w-sm/main:[–thread-content-margin:var(–thread-content-margin-sm,calc(var(–spacing)*6))] @w-lg/main:[–thread-content-margin:var(–thread-content-margin-lg,calc(var(–spacing)*16))] px-(–thread-content-margin)"> <div class="[–thread-content-max-width:40rem] @w-lg/main:[–thread-content-max-width:48rem] mx-auto max-w-(–thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="155db9af-31a7-4138-b77f-20d5bc86f5ae" data-message-model-slug="gpt-5-5" data-turn-start-message="true"> The presence of martyrdom in Algerian poetry embodies national memory and collective consciousness, as the value of martyrdom transcends the historical event to become an existential and spiritual experience. This study aims to analyze the poem “Al-Shahada” by Ammar Ben Laqrichi from an integrated semiotic perspective that combines internal rhythm, poetic imagery, symbolism, and the hermeneutic dimension of martyrdom. The study reveals how internal rhythm, repetition, and semantic stress construct a poetic structure that elevates the self toward martyrdom, and how symbols associated with innocence, the land, the sun, and the vine transform into instruments for shaping the meanings of immortality and spiritual triumph.